2007
DOI: 10.3171/ped.2007.106.6.441
|View full text |Cite
|
Sign up to set email alerts
|

Spinal deformities following selective dorsal rhizotomy

Abstract: There was a high rate of radiologically documented deformities in patients with CP who underwent SDR. Ambulatory function, CP severity, age at surgery, and sex may be contributing factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 45 publications
3
61
1
1
Order By: Relevance
“…However, there is conflicting evidence with respect to possible associations between the presence of pelvic obliquity and hip dislocation and the onset and progression of scoliosis [51]. In addition, some children undergoing selective dorsal rhizotomy appear to be at some risk for the development of scoliosis and other spinal deformities [30,50,41,101,103,109]. Similarly, there are conflicting reports regarding the use of intrathecal Baclofen and its effects on the progression of scoliosis [29,93,94,97].…”
Section: Spinementioning
confidence: 99%
“…However, there is conflicting evidence with respect to possible associations between the presence of pelvic obliquity and hip dislocation and the onset and progression of scoliosis [51]. In addition, some children undergoing selective dorsal rhizotomy appear to be at some risk for the development of scoliosis and other spinal deformities [30,50,41,101,103,109]. Similarly, there are conflicting reports regarding the use of intrathecal Baclofen and its effects on the progression of scoliosis [29,93,94,97].…”
Section: Spinementioning
confidence: 99%
“…8 We attribute this lower level of spinal deformity to the fact that we offer this surgery to ambulatory patients predominantly, that the laminotomy is purposefully narrow given that the stimulation and lesioning is performed on rootlets suspended outside the canal, and finally to the 3-point-perlevel fixation of the laminoplasty.…”
mentioning
confidence: 99%
“…Long-term influence on ICF activity and participation domains and risk of spinal anomalies after SDR remain uncertain. The level of evidence produced by these studies was poor to moderate with 18 Level IV studies [8][9][10][11][13][14][15][16][17][18][20][21][22][23][24][25][26] unable to evaluate causation and three Level III studies 12,19,27 able to provide tentative conclusions that the outcomes were attributable to the SDR.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…Six studies reported adverse events after a follow-up time of more than 5 years. 8,11,13,15,26,28 The follow-up times ranged from 5.8 to 21.4 years. All studies focused on the presence of spinal abnormalities and back pain.…”
Section: What Forms and Magnitudes Of Complications Have Been Documenmentioning
confidence: 99%